2001
DOI: 10.1046/j.1525-139x.2001.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Compliance in Dialysis Patients: Does Anything Work?

Abstract: Noncompliance with prescribed therapy significantly impacts dialysis patient care and outcome. At least one-half of hemodialysis (HD) patients are likely to be noncompliant with some part of their treatment regimen, and one-third of peritoneal dialysis (PD) patients are believed to miss prescribed exchanges. Psychosocial issues, younger age, and smoking behavior have been linked with compliance problems in multiple studies. Few interventions have been rigorously tested, but patient education and/or individuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 22 publications
2
53
0
4
Order By: Relevance
“…Other studies have also reported that older age was associated with higher compliances to fluid restriction and medication prescription [24], [36][37]. Possible explanations are older patients may have more structured lifestyle that accommodates the demands of the treatment regimen while younger patients may perceive themselves as less vulnerable to negative health outcomes [38], confirming the existence of an “intentional noncompliance” [39]. The finding that younger patients were more likely to be non-compliant to treatment recommendation may lead to the future poorer quality of life and higher rates of mortality among these dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported that older age was associated with higher compliances to fluid restriction and medication prescription [24], [36][37]. Possible explanations are older patients may have more structured lifestyle that accommodates the demands of the treatment regimen while younger patients may perceive themselves as less vulnerable to negative health outcomes [38], confirming the existence of an “intentional noncompliance” [39]. The finding that younger patients were more likely to be non-compliant to treatment recommendation may lead to the future poorer quality of life and higher rates of mortality among these dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…As with most chronic diseases, there is an inevitable tension between treatmentrelated constraints and side effects and the patient's desire to maintain a normal life (Kutner, 2001). In the context of breast cancer treatment, this balancing act often involves trading off toxicity concerns against survival and quality-of-life benefits (Chung & Carlson, 2003;Detmar, Muller, Schnornagel, Wever, & Aaronson, 2002).…”
Section: Cancer Treatment Considerations Effects and Side Effectsmentioning
confidence: 99%
“…Compliance literatures also offer a mixed picture, with knowledge-based interventions being intermittently successful; writers have noted that even when information is effectively communicated, knowledge may be variably important (Kutner, 2001;Wolcott, Maida, Diamond, & Nissenson, 1986), and it has been suggested that the consideration of other factors is needed (Wang et al, 2002).…”
Section: Cognitive Variablesmentioning
confidence: 99%
“…It has been estimated that more than 50% of hemodialysis patients are nonadherent in some manner within a one-month time period [1] and upwards of 70% of patients fail to adequately restrict their fluid intake [2]. These rates are alarming, particularly with the consideration that even occasional episodes of serious noncompliance can have severe adverse effects.…”
Section: Introductionmentioning
confidence: 99%